Triple bottom line as a tool for Organizational Job commitment of Employees: Mediating role of Self Esteem - Khilji, Ahmad Bilal; Cheema, Naseer Haider; Noreen, Farzana; Faheem, Amina (International Journal of Psychosocial Rehabilitation, 2020)
The study extends the literature of evolving concept of Sustainability to address the importance with the novel stance is presented here in the form of Triple bottom line which is interrelated concept of sustainability, and prescribes that organizations resolve to concentrate on social and natural concerns similarly as they do on benefits. The thought that we can deal with an organization in a manner that gains monetary benefits as well as improves individuals’ lives and the planet. The triple bottom line construct through the lens of Human resource perspective broadens the scope of the sustainability. This investigation with each dimension of TBL structure studied separately under the positivism stance and highlight that sustainability not only consider in exterior performance of the organization but it is a component for internal dynamism to apply on workforce for their commitment which encourage the organizational performance that leads towards the sustainable development. The data was collected from the manufacturing sector of South Punjab the second largest industrial region of Pakistan. The approved survey was utilized for the collection of data from 151 out of 170 respondents. The simple random sampling technique was applied on supervisors, team leaders, foremen and other first line managers. The Multiple regression analysis, Pearson correlation and for mediation Hayes process was run, which shows that triple bottom line practices have significant impact on job commitment of employees. The Triple bottom line practices have significant impact on Self Esteem of Employee’s and Self-esteem mediates the relation between TBL and Job Commitment of Employees. The study is useful and prolific for Strategic Human Resource affairs, Policy makers and for other stakeholders of the organizations. The study will open the new induction of strategic human resource practices in future for replacing low effective employees related practices with result-oriented practices. The limitations of study are also discussed.